Stroke thrombectomy catheter for aspiration of refractory or inaccessible clot in acute myocardial infarction - Klaudel, Jacek; Surman, Dariusz; Pawłowski, Krzysztof; Trenkner, Wojciech (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2022)
Despite inconclusive and conflicting results of trials and meta-analyses assessing aspiration thrombectomy in ST-segment elevation myocardial infarction (STEMI), trends toward reduced mortality were observed in the high thrombus burden subgroup [1–3]. With a large thrombus being one of the strongest predictors of the no flow phenomenon, manual thromboaspiration remains an effective method of its prevention, especially in patients who cannot undergo a staged procedure after IIB/IIIA inhibitor administration because satisfactory reperfusion has not been achieved during the initial intervention [4–8]. Since standard monorail coronary aspiration devices are often ineffective in the case of a large thrombus, guide extension catheters have been used for clot extraction. Their bigger lumen comes at a cost of worse trackability and a higher risk of artery dissection [9].